Does balancing gender composition lead to more prosocial outcomes? Experimental evidence of equality in public goods and extraction games from rural Kenya - Masuda, Yuta J.; Waterfield, Gina; Castilla, Carolina; Kang, Shiteng; Zhang, Wei (Elsevier, 2022)
There is resurging interest in community-based natural resource management (CBNRM) as an approach for achieving global biodiversity conservation goals. Yet, CBNRM remains dominated by men, elevating the importance of designing programs that give voice and agency to women. Arguments for increasing gender balance within CBNRM often assume women have strong preferences for equality and altruism and would therefore be better environmental stewards. Evidence on the effect of gender balance on commons management, however, remains mixed. We report on two framed field experimental games with community members directly engaged in the use and management of natural resources in rural Kenya. Participants were randomly assigned to single-gender (all male n = 23; all female n = 28) or mixed gender groups (n = 36) to assess the role of gender composition on group and individual decisions. The two games provide unique insights into the give (public good games) and take (extraction games) decisions common in natural resource management. We find mixed gender groups tend to achieve more socially optimal outcomes than single-gender groups in the public goods game context, but all male groups tended to conserve the most in the extraction game. Women are not necessarily more likely to make prosocial decisions than men, and factors such as framing and social relations affect decisions. Our results indicate gender composition affects group decision-making and is therefore important for commons management, and that mixed gender groups can be more effective than single-gender groups. Improving gender balance in CBNRM may help achieve more desirable outcomes from a social and conservation perspective but understanding decision-making contexts is critical.